MODERNIZATION PROCESSES IN THE MODERN FINE ART - Karabalayeva, B.R.; Pelshe, S.; Seitakhmetova, N.L. (Scientific Journal of Pedagogy and Economics, 2020)
Today, in the visual arts of Kazakhstan, the actual art is developing dynamically. Although the popularity of new technologies has been observed only in the last decade, there are selected, unique works in the actual art of Kazakhstan. The artists received the core of actual art they were interested in from the conceptual art of Russia. It began to expand, because in General, within the framework of conceptual art, social and basic ideas were very well developed. This affected not only the spiritual process, but also people's thoughts. The main search for contemporary art can be observed in the creation of mythological images. The attempt of brush masters to abstract originates from bold fantasies that smoothly pass to iconic images, along with various ways of image; there are attempts to convey the idea of compositional works. In the article, the authors review the space of historical development of the art of Kazakh painting. In addition, the modern art of painting in Portugal is offered as an analysis of the set themes and positions of modern art of painting, comparative analyses are provided. Today’s visual art landmarks will be used to analyze the predictive and critical point of view of the past and future.